Developing Computing Competencies Without Restrictions - Vidal-Silva, Cristian; Barriga, Nicolas; Ortega-Cordero, Franco; Gonzalez-Lopez, Javiera; Jimenez-Quintana, Claudia; Pezoa-Fuentes, Claudia; Veas-Gonzalez, Ivan (IEEE access, 2022)
The information society represents a great revolution. Computing programming is a relevant competence nowadays for everybody, regardless of educational background. However, traditional programming languages consider syntax barriers that complicate their adoption and usefulness for beginners. Python is an exception for its open-source, cross-platform nature and syntax simplicity, which facilitate the development of algorithmic thinking and dissemination of programming solutions. Several Python extensions support modern functionalities such as web development, videogame, and machine learning, making it one of the most used programming languages. Google Colab or Colaboratory facilitates the online learning and development of Python solutions. This article presents positive academic experiences of Chilean students of majors from two Chilean universities, a traditional university in the north and a private university in the middle of Chile, using Google Colab to develop programming competencies remotely for the Covid pandemic. We highlight the promising results obtained for basic programming and operating system programming subjects, which motivate us to use Python and Google Colab widely, not only in university contexts. We expect to continue developing programming competencies using Google Colab and Python. The main limitation encountered in this experience is the internet connection requirements for online education. However, it does not represent an issue for education in developing and developed countries. Google Colab permits the development of highly demanded competencies worldwide at home, only with internet access and a web browse, an excellent motivation for learning for all students regardless of age and academic level.